A one-step method for producing Fe-free α″-Fe 16 N2 Powder Method
By preparing Fe-phase-free α″-Fe16N2 powder in one-step method, the surface preoxidation treatment of nano-scale iron concentrate and the catalytic nitriding of ammonia hydrogen mixture was solved, and the problem of incomplete nitriding and soft magnetic Fe phase in the prior art was achieved, and the preparation of α″-Fe16N2 powder without residual Fe phase was achieved, with higher magnetic properties.
Patent Information
- Application Number
- CN202411826810.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing reduction-nitriding method of preparing α″-Fe16N2 powder has problems such as incomplete nitriding, soft magnetic Fe phase, low reaction rate, high cost and difficult to expand production.
The one-step method is used to prepare Fe-phase-free α″-Fe16N2 powder. By performing surface preoxidation on nano-scale iron concentrate, the surface is converted into iron oxide with high reduction potential energy, achieving one-step reduction and nitriding below 200°C, avoiding the problems caused by multi-stage temperature control, and catalyzed nitriding is carried out through ammonia hydrogen mixture.
The efficient preparation of Fe-phase-free α″-Fe16N2 powder is achieved, and there is no residual soft magnetic Fe phase in the product, which has higher coercive force and permanent magnet performance, simplifying the production process and improving production efficiency.
Smart Images

Figure CN119284845B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a ferromagnetic material, and more particularly to a one-step method for preparing an α″-Fe nitride magnetic material without a soft magnetic Fe phase. 16 The invention relates to a method for preparing N2 powder, and belongs to the technical field of magnetic material preparation. Background Art
[0002] α″-Fe 16 N2 powder has excellent magnetic properties such as high saturation magnetization and moderate magnetocrystalline anisotropy, so it has great advantages in applications such as magnetic recording and magnetic sensing element materials. It is also a potential rare-earth-free permanent magnet material with broad application prospects in place of rare-earth permanent magnets.
[0003] However, existing methods for preparing high-quality α″-Fe 16 The process of N2 powder still faces some challenges, such as low product purity, difficulty in scale-up production, and high cost when using ball milling annealing, sputtering, or ion implantation. 16 The most feasible method for N2 powder is low-temperature reduction-nitridation. This method usually uses nano-Fe3O4 powder as raw material, and performs two reaction steps of hydrogen reduction and ammonia nitridation in a tube furnace. By optimizing process parameters such as reduction temperature, nitridation temperature, reaction time, etc., a higher content of α″-Fe 16 N2 powder. For example, a Chinese patent (publication number: CN114222826A) discloses a coercive force enhanced iron nitride nanoparticle with high saturation magnetization, which has α″-Fe 16 N2 phase, and its saturation magnetization was measured to be about 160emu / g, and its coercivity was about 1000Oe. At the same time, Chinese patents (publication number: CN115699227A), (publication number: CN104240882A) and others also mentioned a similar reduction-nitridation two-step method, but the reduction-nitridation method was used to prepare α″-Fe 16 N2 powder also faces some technical problems. The key limiting link is that the reaction temperature of the nitridation process is below 200°C, the nitridation rate is slow, and the nitridation is often incomplete with the existence of soft magnetic Fe phase, which will affect the product performance. The existing reduction-nitridation two-step method often undergoes a high-temperature hydrogen reduction step and then a low-temperature nitridation step. It is very difficult to cool down the powder after reduction, which is time-consuming and the intermediate product is difficult to preserve. Summary of the invention
[0004] Aiming at the existing reduction-nitridation method to produce α″-Fe 16 The technical defects of N2 powder exist. The purpose of the present invention is to provide a one-step method for producing Fe-free α"-Fe 16The method is to pre-oxidize the surface of nano-sized iron ore to convert it into iron oxide with higher reduction potential, so that it can be reduced and nitrided in one step in an extremely low temperature range below 200°C, thereby avoiding the problems of material transportation and cooling caused by multi-stage temperature control during the reaction. At the same time, the high-activity iron obtained by the reduction reaction is immediately subjected to catalytic nitridation reaction, so that the final α″-Fe 16 N2 powder products do not contain soft magnetic phase Fe and have higher coercive force and permanent magnetic properties.
[0005] In order to achieve the above technical objectives, the present invention provides a one-step method for producing Fe-free α"-Fe 16 The method of N2 powder comprises the following steps:
[0006] 1) The iron ore concentrate is activated by two-stage wet grinding to obtain nano-scale iron ore concentrate powder slurry;
[0007] 2) placing the nano-scale iron ore concentrate powder slurry in an oxygen-containing atmosphere and performing a drying pre-oxidation treatment at a temperature of 80°C to 120°C to obtain a nano-scale iron ore concentrate powder with a surface layer of Fe2O3;
[0008] 3) Place the nano-sized iron ore concentrate powder with a surface layer of Fe2O3 in an ammonia-hydrogen mixed gas environment and perform a reduction-nitridation reaction at a temperature of 120-200°C to obtain Fe-free α″-Fe 16 N2 powder; the ammonia-hydrogen mixed gas contains the following components in volume percentage: 85-95% ammonia, 5-10% hydrogen, less than 0.1% water vapor, and the remaining gases are inert gases.
[0009] The one-step method provided by the present invention produces Fe-free α"-Fe 16The method of preparing N2 powder comprises the following steps: firstly grinding and activating the iron concentrate to obtain nano-scale iron concentrate powder with high reactivity; and the nano-scale iron concentrate powder can oxidize the surface ferroferric oxide into ferrous oxide during the drying process; on the one hand, ferrous oxide with high activity and high reduction potential is easy to undergo reduction reaction compared with ferrous oxide, so that hydrogen reduction can be started at a lower temperature and subsequent reduction reaction can be induced, which is conducive to the completion of hydrogen reduction and nitridation process in one step below 200°C; in particular, the high-activity iron generated by low-temperature reduction can be directly and efficiently nitrided, which solves the technical problems of low iron nitridation reaction rate, incomplete reaction and existence of soft magnetic Fe phase during the step-by-step hydrogen reduction and nitridation reaction; and at the same time, it also solves the technical problems that the high-temperature reduced iron powder needs to be cooled before nitridation, which is difficult to cool down, takes a long time, is difficult to store in the middle, and the activity of the reduced iron is partially lost. On the other hand, the low-temperature reduction path of iron ore concentrate is Fe2O3-Fe3O4-Fe, without going through the ferrous process. The overall structure of the particles has not changed. After the reduction-nitridation process, the product naturally forms a 0-9% Fe3O4 inside and a pure phase α″-Fe outside. 16 N2 core-shell structure product, which is in the presence of pure α″-Fe 16 N2 has better magnetic properties, especially compared with α″-Fe with some soft magnetic phase. 16 The advantage of N2 is more obvious, mainly reflected in its higher coercivity. The key to the reduction-nitridation reaction of the present invention is to ensure that the nitridation potential is always greater than the reduction potential by regulating the atmosphere and coordinating the temperature and other conditions, so that the Fe phase generated by the reduction process can be nitrided to generate α″-Fe 16 N2, there is no residual soft magnetic Fe phase in the final product.
[0010] As a preferred solution, the iron concentrate is an iron oxide mineral with an iron grade of more than 70.5% and a non-oxygen impurity content of no more than 1%. The iron concentrate is a high-purity iron concentrate after deep purification, with an iron grade of more than 70.5%, a non-oxygen impurity content of no more than 1%, and a total mass content of Ni, Mn, Al and their oxides of no more than 0.8%. The key impurity elements in the iron concentrate will affect the product, mainly soft magnetic elements such as Ni, and also include elements such as Mn and Al, and their total amount should not be higher than 0.8%.
[0011] As a preferred solution, the two-stage wet grinding activation adopts nano sand milling, with water as solvent, the first stage grinding is configured with grinding beads with a particle size of 0.2-0.5 mm, the grinding speed is 1000-2000 r / min, and the grinding is performed until D 50 The particle size is in the range of 200~500nm. The second stage of grinding is equipped with grinding beads with a particle size of 0.05~0.2mm, and the particles are ground to D 50The particle size is in the range of 60-100 nm. The grinding beads are preferably zirconium grinding beads. The nano-scale iron ore concentrate powder D obtained after grinding 50 The particle size is between 60 and 100 nm. It has ultra-high reactivity, and its thermogravimetric oxidation reaction rate in air at 100°C should be higher than 10% / min. The grinding and activation process involves particle refinement and activation. Since the particle size of ultra-pure iron concentrate raw materials is usually above 30µm, it is suitable to use grinding beads with a particle size of 0.2~0.5mm for coarse grinding. To further grind the nano-sized iron concentrate powder to a particle size of D 50 When the particle size reaches 60~100nm, it is necessary to further use grinding beads with a particle size of 0.05~0.2mm for secondary fine grinding to obtain nano-scale iron ore concentrate powder with a lower particle size.
[0012] As a preferred solution, the drying pre-oxidation treatment time of the nano-scale iron ore concentrate powder slurry is 5 to 60 minutes. The nano-scale iron ore concentrate powder based on the grinding activation treatment has high reactivity, so it can be dried in an oxygen-containing atmosphere at a relatively low temperature to complete the pre-oxidation treatment, so that the surface of the nano-scale iron ore concentrate powder is oxidized to Fe2O3, and by controlling the drying pre-oxidation time and other conditions, the mass ratio of Fe2O3 on the surface of the nano-scale iron ore concentrate powder can be controlled to be not less than 20%. It is conducive to the subsequent hydrogen reduction and nitridation process. The drying pre-oxidation process can adopt conventional forced air drying, exhaust air drying or drying under low pressure.
[0013] The ammonia hydrogen mixed gas of the present invention comprises the following volume percentage components: ammonia 85~ 95%, hydrogen 5%~10%, water vapor less than 0.1%, and the remaining gases are inert gases. Inert gases such as argon. The reduction-nitridation process of iron oxides is realized by using a mixed atmosphere of ammonia and hydrogen, wherein it is necessary to ensure that the nitridation potential energy is always greater than the reduction potential energy in the reaction, so as to ensure that the reduced iron is completely nitrided, and the volume ratio of ammonia is set to 85~95%, and the volume ratio of hydrogen is 5%~10%, and coordinated with the reaction temperature and pressure at the same time. The water ratio in the reaction gas will also affect the reduction potential energy, and the water ratio is controlled to be not higher than 0.1%, and the suitable content is 0.03~0.05%. The water mainly comes from ammonia, and the control method is to set a dry separator.
[0014] As a more preferred solution, the pressure of the ammonia-hydrogen mixed gas is 0.1-0.5 MPa. The reaction rate will be faster under high pressure reaction.
[0015] As a preferred solution, the reduction-nitridation reaction time is 14 to 30 hours.
[0016] The reduction-nitridation reaction of the present invention is implemented by a rotary reactor, in particular, a tubular furnace that can rotate or reverse. The production furnace adopts precise electric heating or oil bath / sand bath heating, and the temperature error is precisely controlled to be no more than 1°C. The reaction process is highly sensitive to temperature and requires precise temperature control equipment. It is suitable to use a rotating or reversing tubular furnace as the reaction equipment. The reduction-nitridation reaction is an endothermic process, and the required energy supplement in the reactor is relatively large. It is advisable to use precise electric heating or high-temperature oil bath / sand bath as heat supplement for the reaction system. The charge amount in the rotary reactor is about 10%~20%, which is the suitable range for the production of powder materials in a rotary furnace.
[0017] The Fe-free α″-Fe 16 N2 powder refers to α″-Fe 16 The purity of N2 phase is >90% (mass content), the purity of Fe3O4 phase is no more than 9%, and the rest is impurities of the raw materials themselves, and there is no Fe residual in the product. In the present invention, the reduction reaction of the iron oxide particles is limited so that no Fe is left. The Fe-free α″-Fe 16 The Fe3O4 in N2 powder only exists inside the particles, and the powder presents Fe4O3 phase as the core and α″-Fe 16 N2 is the outer shell structure. It should be noted that the present invention can also completely convert Fe3O4 by controlling the hydrogenation-nitridation reaction conditions to obtain pure α″-Fe 16 N2 powder.
[0018] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0019] 1) The present invention adopts a one-step method to produce Fe-free α″-Fe 16 The N2 powder model, that is, only one reaction temperature and atmosphere need to be controlled during the production process, simplifies the production process, especially avoids the long cooling stage in the middle of the conventional reduction-nitridation production process, and greatly improves production efficiency.
[0020] 2) The present invention uses ammonia-hydrogen mixed gas for a one-step reaction, and controls the nitridation potential energy to be always greater than the reduction potential energy, so that the Fe phase generated by the reduction during the reaction can be nitrided to generate α″-Fe 16 N2, there is no residual soft magnetic Fe phase in the final product. By controlling the reaction parameters, the product can be controlled to have a core-shell structure with a permanent magnetic iron oxide phase inside, and the magnetic properties of the product are better.
[0021] 3) The present invention uses nanomechanical activation and low-temperature pre-oxidation to improve the activity of the iron oxide raw material, and the reduction and nitridation reactions are carried out in the same reactor, which can more effectively utilize the activity of the reduced iron, and the reaction rate is faster, and the reaction can be completed within 30 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Preparation of α″-Fe for Example 1 16 XRD pattern of N2 powder, in which there is almost no Fe phase and the content is less than 0.1%.
[0023] Figure 2 α″-Fe prepared in Comparative Example 1 16 The XRD image of N2 powder shows that the iron concentrate is completely reduced and does not contain ferrous or other iron oxide phases, but the nitridation process is not complete and contains 10% Fe phase. DETAILED DESCRIPTION
[0024] In order to more clearly understand the present invention, specific embodiments are now used to more clearly explain and analyze the contents of the present invention. However, the claims of the present invention are not limited to the following example methods and conditions. Other examples obtained by relevant technical personnel in the field without creative work are all within the protection scope of the present invention.
[0025] Example 1
[0026] The ultra-pure iron concentrate obtained by deep beneficiation is selected as the raw material, with an iron grade of 72.1% and the total content of other impurities (acid insoluble matter) of only 0.47%, containing 0.1% Ni, 0.3% Al2O3, 0.24% Mn, and an initial particle size of D 50 The material was finely ground in a nano sand mill, with a grinding speed of 1700r / min, 0.2~0.3mm zirconia balls, pure water as solvent, and a solid-liquid mass volume ratio of 1g:2mL. After 4 hours of grinding, the particle size D 50 =200nm ultrafine particle slurry, then enter the second stage grinding, the speed is 2400r / min, the grinding beads are 0.05mm zirconia balls, pure water is the solvent, the solid-liquid mass volume ratio is 1g:10mL, after 3 hours of grinding, the particle size D 50 =65nm ultrafine particle slurry. The slurry is dried in an oven to obtain powder, the drying temperature is set to 80°C, and the exhaust drying method is adopted. Drying for 60 minutes to obtain dry powder.
[0027] After the dry powder is dispersed, the material is reacted in a rotary tube. The rotary tube is set in an oil bath. The oil bath reaction temperature is set to 120°C. The ammonia hydrogen reaction gas introduced is 85% ammonia and 10% hydrogen. The low-temperature reaction time is long. 5% argon is introduced to improve the safety of the reaction equipment. The pressure of the mixed gas is 0.5MPa. The moisture content of high-quality liquid ammonia is 0.01% after drying. The moisture content in hydrogen is 20ppm. The material amount is 10% of the volume of the rotary furnace. The product is obtained after 30 hours of reaction. The prepared α″-Fe 16 N2 powder XRD pattern Figure 1As shown, there is almost no Fe phase, the content of which is less than 0.1%. At this time, the coercive force of the product VSM powder detected is 1350Oe.
[0028] Example 2
[0029] The ultrapure iron concentrate obtained by deep beneficiation in Example 1 was selected as the raw material, and the initial particle size D 50 The material was finely ground in a nano sand mill, with a grinding speed of 1700r / min, 0.5mm zirconia balls, pure water as solvent, and a solid-liquid mass volume ratio of 1g:1mL. After 3 hours of grinding, the particle size D 50 =500nm ultrafine particle slurry, then enter the second stage grinding, the speed is 2700r / min, the grinding beads are 0.1~0.15mm zirconia balls, pure water is the solvent, the solid-liquid mass volume ratio is 1g:8mL, after 2 hours of grinding, the particle size D 50 = 100nm ultrafine particle slurry. The slurry is dried in an oven to obtain powder, the drying temperature is set to 110°C, and the blast drying method is used. Dry powder is obtained by drying for 5 minutes.
[0030] After the dry powder is broken up, the material is reacted in an electric heating rotary kiln. The sand bath reaction temperature is set to 195°C. The ammonia-hydrogen reaction gas introduced is 95% ammonia, 5% hydrogen, and about 0.02% water vapor. The pressure of the mixed gas is 0.1MPa. The material volume is 20% of the rotary kiln volume. The product is obtained after 14 hours of reaction. There is some unreduced Fe3O4 in the prepared product, with a content of about 8%, which exists inside the core-shell structure, and the outside is pure phase α″-Fe 16 N2 phase and no Fe phase exists. Due to the existence of internal iron oxide, the magnetic properties of the final product, especially the coercive force data, are better. The coercive force of the powder VSM test product is 2100Oe.
[0031] Comparative Example 1
[0032] Compared with Example 2, the only difference is that a two-step method is used for hydrogen reduction and nitridation.
[0033] The process of hydrogen reduction and nitridation is as follows: the reduction temperature is set at 400°C, 100% hydrogen is introduced, reduction is performed for 3 hours, cooling is performed under a nitrogen atmosphere, and then 100% ammonia is introduced, and nitridation is performed at 200°C for 14 hours to obtain the product. The prepared α″-Fe 16 N2 powder XRD pattern Figure 2 As shown, the iron concentrate is completely reduced and does not contain ferrous or other iron oxide phases, but the nitridation process is not complete and contains 10% Fe, which has a significant impact on product performance, mainly reflected in the coercivity of the prepared powder in the VSM test of only 640Oe.
[0034] Comparative Example 2
[0035] Compared with Example 2, the only difference is that the hydrogen reduction-nitridation conditions are different.
[0036] The hydrogen reduction-nitridation conditions are as follows: the sand bath reaction temperature is set at 195°C, the ammonia-hydrogen reaction gas introduced is 85% ammonia, 15% hydrogen, and about 0.02% water vapor, the pressure of the mixed gas is 0.41 MPa, the feed amount is 20% of the rotary kiln volume, and the product is obtained after 14 hours of reaction.
[0037] The product is mostly Fe phase, with only a trace amount of α″-Fe 16 In the N2 phase, due to the high proportion of hydrogen, the reaction is controlled so that the reduction potential is greater than the nitridation potential, and the nitridation potential is too low, resulting in almost no nitridation reaction and the product is Fe.
[0038] Comparative Example 3
[0039] Compared with Example 1, the only difference is that the hydrogen reduction-nitridation conditions are different.
[0040] The conditions for hydrogen reduction-nitridation are: the sand bath reaction temperature is set at 120°C, the ammonia-hydrogen reaction gas is 98% ammonia and 2% hydrogen, the pressure of the mixed gas is 0.5MPa, the feed volume is 20% of the rotary kiln volume, and the product is obtained after 100h of reaction. Most of the raw materials are converted into Fe3O4, but only less than 10% of Fe and α″-Fe 16 N2 conversion, the reaction was unsuccessful.
[0041] Comparative Example 4
[0042] Compared with Example 1, the only difference is that the drying and pre-oxidation conditions are different.
[0043] The vacuum drying method under non-oxidizing atmosphere is adopted. It takes 50 hours for the reaction to obtain the pure phase product, and the overall reaction rate is very slow.
Claims
1. A one-step method for producing Fe-free α″-Fe 16 The method of N2 powder is characterized in that: The following steps are involved: 1) The iron ore concentrate is activated by two-stage wet grinding to obtain nano-scale iron ore concentrate powder slurry; 2) placing the nano-scale iron ore concentrate powder slurry in an oxygen-containing atmosphere and performing a drying pre-oxidation treatment at a temperature of 80°C to 120°C to obtain a nano-scale iron ore concentrate powder with a surface layer of Fe2O3; 3) Place the nano-sized iron ore concentrate powder with a surface layer of Fe2O3 in an ammonia-hydrogen mixed gas environment and perform a reduction-nitridation reaction at a temperature of 120-200°C to obtain Fe-free α″-Fe 16 N2 powder; the ammonia-hydrogen mixed gas contains the following components in volume percentage: 85-95% ammonia, 5-10% hydrogen, less than 0.1% water vapor, and the remaining gases are inert gases.
2. A one-step method for producing Fe-free α″-Fe 16 The method of N2 powder is characterized in that: The iron concentrate is an iron oxide mineral with an iron grade of more than 70.5% and a mass content of non-oxygen impurities of no more than 1%.
3. A one-step method for producing Fe-free α″-Fe 16 The method of N2 powder is characterized in that: The two-stage wet grinding activation adopts nano sand grinding, with water as solvent. The first stage of grinding is equipped with grinding beads with a particle size of 0.2-0.5 mm, and the grinding speed is 1000-2000 r / min. Grind to D 50 The particle size is in the range of 200~500nm. The second stage of grinding is equipped with grinding beads with a particle size of 0.05~0.2mm, and the particles are ground to D 50 The particle size is in the range of 60~100nm.
4. A one-step method for producing Fe-free α″-Fe 16 The method of N2 powder is characterized in that: The drying pre-oxidation treatment time of the nano-scale iron ore concentrate powder slurry is 5 to 60 minutes.
5. A one-step method for producing Fe-free α″-Fe 16 The method of N2 powder is characterized in that: The pressure of the ammonia-hydrogen mixed gas is 0.1-0.5 MPa.
6. A one-step method for producing Fe-free α″-Fe 16 The method of N2 powder is characterized in that: The reduction-nitridation reaction time is 14 to 30 hours.
Citation Information
Patent Citations
Iron nitride based magnetic powder and magnet using the same
CN104240882A
Coercive force enhanced iron nitride nanoparticles with high saturation magnetization
CN114222826A
Anisotropic iron nitride permanent magnet
CN115699227A
Ferromagnetic particle powder, method for producing same, anisotropic magnet and bonded magnet
CN102576591A
Reduced iron or iron nitride preparing method
CN109402315A